FAKTOR-FAKTOR YANG MEMENGARUHI PERMINTAAN BUAH ANGGUR IMPOR DI TRANSMART CARREFOUR KOTA PALU - Ningsih, Sri Rahmadhi; Hatmi, Wira (Fakultas Pertanian, Universitas Tadulako, 2024)
This study aimed to examines the factors that influence the demand for imported grapes at Transmart Carrefour in Palu City. The research was conducted in August to September 2021 and involved 30 grape consumers who were selected randomly. The study used the Multiple Linear Regression analysis to identify the relationships between various factors, including income, grape prices, apple prices, family size, and consumer preferences. The results showed that all five factors together have a significant impact on grape demand, with a perfect correlation between the variables (R² value of 1.000). Additionally, the analysis revealed that individual factors such as income, grape prices, and consumer preferences have a significant influence on grape demand, whereas apple prices and family size do not.